1968
DOI: 10.1099/0022-1317-3-1-97
|View full text |Cite
|
Sign up to set email alerts
|

The Morphological and Biological Effects of Various Antisera on Avian Infectious Bronchitis Virus

Abstract: SUMMARYmologically, homotypic and heterotypic antisera neutralized avian infectious bronchitis virus significantly more when unheated. Morphologically, using the electron microscope technique of negative staining, there was a clear distinction between the effects of homotypic and heterotypic antisera. Heated homotypic antiserum revealed antibody attached only to the projections of the virus, while with unheated homotypic serum heat labile components could be visualized but no basic change could be seen in part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
57
0

Year Published

1969
1969
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(60 citation statements)
references
References 3 publications
3
57
0
Order By: Relevance
“…Since C3 products are deposited and covalently bind to surfaces in a spatial distribution surrounding each C-activating immune complex, it is likely that some of the C3 fragment molecules become bound to viral structures involved in attachment to and/or penetration of B lymphocytes. This mechanism of complement-dependent viral neutralization has been observed with other viruses and is most likely the mechanism of IgM and complement-mediated inactivation of avian infectious bronchitis virus (32), HSV (33)(34)(35), Newcastle disease virus (36), equine arteritis virus (37), vesicular stomatitis virus (38), and vaccinia virus (39). Studies with complement components with some of these viruses show that herpes simplex I (33) and equine arteritis viruses (37) can be neutralized by antibody together with Cl and C4 but these viruses and also Newcastle disease virus (36), vesicular stomatitis virus (38), and vaccinia virus (39) are more efficiently neutralized in the presence of Cl, C4, C2, and C3.…”
Section: Resultsmentioning
confidence: 69%
“…Since C3 products are deposited and covalently bind to surfaces in a spatial distribution surrounding each C-activating immune complex, it is likely that some of the C3 fragment molecules become bound to viral structures involved in attachment to and/or penetration of B lymphocytes. This mechanism of complement-dependent viral neutralization has been observed with other viruses and is most likely the mechanism of IgM and complement-mediated inactivation of avian infectious bronchitis virus (32), HSV (33)(34)(35), Newcastle disease virus (36), equine arteritis virus (37), vesicular stomatitis virus (38), and vaccinia virus (39). Studies with complement components with some of these viruses show that herpes simplex I (33) and equine arteritis viruses (37) can be neutralized by antibody together with Cl and C4 but these viruses and also Newcastle disease virus (36), vesicular stomatitis virus (38), and vaccinia virus (39) are more efficiently neutralized in the presence of Cl, C4, C2, and C3.…”
Section: Resultsmentioning
confidence: 69%
“…Isaacs and colleagues have shown that anti-A33 in combination with complement (C1q and C5) efficiently mediates EV destruction (67). Complement-dependent virolysis is also effective against other families of viruses (106)(107)(108)(109)(110). It is also possible for complement to disrupt the EV outer membrane but not inner membrane and allow access of anti-MV Abs to neutralize the virus, as shown by experiments in which EV neutralization was dependent on the concurrent presence of anti-MV Abs (59).…”
Section: Discussionmentioning
confidence: 99%
“…Although the role of complement is generally attributed to an increase in the bulk of protein on the virion surface which hinders absorption, it may enhance virus neutralization by directly lysing the virus-antibody mixture as has been shown for many enveloped viruses including avian infectious bronchitis virus (Berry & Almeida, 1968), mouse leukaemia virus (Oroszlan & Gilden, 1970), Moloney leukaemia virus (Oldstone, 1975) and rubella virus (Schluederberg et al, 1976). In addition, complement may enhance neutralization by facilitating the agglutination of antibody-coated virions (Oldstone et al, 1974).…”
Section: Discussionmentioning
confidence: 99%